КҮРДЕЛІ ҚҰРЫЛЫСТЫ ҰЙЫМДАСТЫРУ ЕРЕКШЕЛІКТЕРІ (Journal of Economic Research & Business Administration, 2015)
The article is devoted to the specifics of the organization of capital construction in the Republic of Kazakhstan. It discusses the basic concepts of capital construction and basic accounting issues in construction organizations.